2020
DOI: 10.1055/s-0040-1710107
|View full text |Cite
|
Sign up to set email alerts
|

Management of Idiopathic Intracranial Hypertension: Experience of a North African Center

Abstract: Background The idiopathic intracranial hypertension (IIH) is characterized by elevation of intracranial pressure (ICP) in the absence of intracerebral space occupation or venous sinus thrombosis. It usually occurs in obese young women but is very rare in childhood. Materials and Methods We conducted a retrospective study in the neurosurgical department of Bab El Oued teaching hospital of Algiers over a period of 8 years from January 2008 to December 2015. We analyzed clinical data of 10 patients with IIH diagn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…A study in North India found a higher frequency of IIH in patients with chronic daily headache compared with Western populations (30). The mean age at diagnosis was 43.32 AE 12.38 years, whereas previous population-based studies reported an age range of 23 to 36 years for IIH (31)(32)(33). The mean age at diagnosis in Turkey was higher than reported, although some patients were admitted for follow-up visits.…”
Section: Discussionmentioning
confidence: 88%
“…A study in North India found a higher frequency of IIH in patients with chronic daily headache compared with Western populations (30). The mean age at diagnosis was 43.32 AE 12.38 years, whereas previous population-based studies reported an age range of 23 to 36 years for IIH (31)(32)(33). The mean age at diagnosis in Turkey was higher than reported, although some patients were admitted for follow-up visits.…”
Section: Discussionmentioning
confidence: 88%